Structure and ontogeny of Swartzia langsdorffii (Leguminosae) pericarp - Colpas, F. T.; Oliveira, DMT (Wiley-Blackwell, 2002)
In order to elucidate the position of the Swartzieae in Leguminosae, Swartzia langsdorffii was chosen as a representative of this tribe type genus and subjected to structural studies of immature ovaries (in the floral bud and flowers) and developing and mature fruits. The external epidermis of the ovary is characterized by one layer of thin-walled polyhedral cells with a thin cuticle. Parenchyma cells have a large quantity of tannin-containing idioblasts located inside a procambial ring. The one-layered inner epidermis consists of flattened cells. In fruits the one-layered exocarp is covered by a thick cuticle. The mesocarp consists of three distinct regions, the middle region being a sclerenchymatous layer. The one-layered endocarp shows cells with little cohesion. The occurrence of canals consisting of a net of resinous cells was also observed in the mesocarp. Secretion was of an elaborate composition. Differentiation of the secretory structures begin in the floral bud ovary, where they appear as idioblasts containing tannin. The taxonomic position of this tribe, as well as the function of the mesocarp secreting canals, are discussed.